2008
DOI: 10.1038/sj.bjc.6604343
|View full text |Cite
|
Sign up to set email alerts
|

Expression of methylation-related genes is associated with overall survival in patients with non-small cell lung cancer

Abstract: The abnormality of DNA methylation is involved in tumour progression, and thus has a modulating effect on clinical outcome of cancer patients. In this study, we measured the mRNA expression levels of three methylation-regulating genes (DNMT1, DNMT3b, and MBD2) in 148 tumour samples from patients with non-small cell lung cancer (NSCLC) using quantitative real-time polymerase chain reaction and then determined their prognostic values. Our data showed that the high level of DNMT1 expression was significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
3
25
1
Order By: Relevance
“…The Cox regression analysis revealed that DNMT1 was an independent prognostic factor, which suggests that DNMT1 expression may be a suitable prognostic marker for patients with PGI-DLBCL. These findings are consistent with those of other previous studies (28)(29)(30)(31)(32)(33)(34)(35)(36). Although previous studies have reported that the levels of DNMT3a and DNMT3b were significantly higher in cancer patients (31,33,35,36), the present study indicated that the expression of DNMT3a and DNMT3b in PGI-DLBCL patients was markedly lower than that of the healthy controls.…”
Section: Overall Survivalsupporting
confidence: 79%
See 2 more Smart Citations
“…The Cox regression analysis revealed that DNMT1 was an independent prognostic factor, which suggests that DNMT1 expression may be a suitable prognostic marker for patients with PGI-DLBCL. These findings are consistent with those of other previous studies (28)(29)(30)(31)(32)(33)(34)(35)(36). Although previous studies have reported that the levels of DNMT3a and DNMT3b were significantly higher in cancer patients (31,33,35,36), the present study indicated that the expression of DNMT3a and DNMT3b in PGI-DLBCL patients was markedly lower than that of the healthy controls.…”
Section: Overall Survivalsupporting
confidence: 79%
“…Another study identified that the level of DNMT1 mRNA was significantly higher in gastric cancer patients with methylated Runx3, compared with those with unmethylated Runx3 (30). Furthermore, increased expression of DNMT1 and DNMT3b have been detected in the tumor tissues of patients with lung cancer, and were also associated with poorer prognoses (31)(32)(33)(34). In a study concerning pancreatic cancer patients, those with a higher DNMT1 expression exhibited a lower overall survival rate (35).…”
Section: Overall Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of DNMT3B correlated with poor survival in our NSCLC set, and this is in agreement with a previous study demonstrating prognostic significance of DNMT3B expression but only in younger patients aged <65 years. 51 The potential clinical implementation of these observations should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas DNMT1 has a preference for hemimethylated DNA and is involved in the maintenance of methylation, DNMT3A and DNMT3B function as de novo methyltransferases. Increased expression of one or more of the DNMT has been reported at a number of sites of cancer and has been shown to be an adverse prognostic factor (1,23,39).…”
mentioning
confidence: 99%